A new species of the genus Ilyocryptus Sars, 1862 (Cladocera: Anomopoda: Ilyocryptidae) from the East Asian Palaearctic - Jeong, Hyun Gi; Kotov, Alexey A.; Lee, Wonchoel (Zootaxa, 2012)
A new Palaearctic species of the genus Ilyocryptus Sars, 1862 (Cladocera: Anomopoda: Ilyocryptidae) is described basedon samples from Republic of Korea, Japan, and the Far East of Russia. This taxon was mis-identified by some previousauthors as I. agilis Kurz, 1878. Among the agilis-like species sensu Kotov & Elías-Gutiérrez (2009), I. yooni sp.nov. isunique in absence of any setules or denticles near preanal teeth on the postabdomen. It also differs from its closest relativeI. agilis s.str. in (1) a more sharp dorsal keel; (2) short setae at postero-ventral portion of valve; (3) a long abdominalprojection; (4) presence of spinules on internal wall of anus; (5) shorter antenna I; (6) distal burrowing spine not projectedbehind distal end on basal segment of antenna II; (7) spine on proximal segment of antennal exopod not longer than thenext segment; (8) setae at bases of the flap at inner-distal portion of limb III of different size and armature. Apparently I. yooni sp. nov. is a member of the Far East endemic species complex, recently defined by Kotov et al. (2011, 2012).